The Chinese University stakeholder satisfaction survey: Developing a customer-centered self-assessment tool for higher education quality management - Pan, Feng; Liu, Liu; Wang, Zhen (Frontiers in Psychology, 2022)
Customer-centred management philosophy is a core theory in corporate management. To increase the quality of higher education in China and to promote sustainable development, this study used customer-centred enterprise management theory and focused on a university in China, surveying nearly 3,000 students, teachers, staff, and human resources personnel. A stakeholder satisfaction questionnaire was designed as the research tool to survey self-assessed innovative management inside the university. Three internal self-assessment tools were designed, namely the China University Student Satisfaction Survey Scale, the China University Teacher and Staff Satisfaction Survey Scale, and the China University Graduate Human Resources Department Satisfaction Survey Scale. According to this study, (1) introducing the customer-centred theory of corporate management into the study of higher education management in China is bold and innovative; doing this could promote improved quality in China’s higher education system and enable sustainable development. (2) This study adopted a vigorous method, and the internal management tools for Chinese universities exhibited well-developed structures and informative items reflecting the goals of the survey and effectively promote management innovation. (3) The internal management tools designed in this study required further assessment for increased comprehensiveness. Relevant thoughts and philosophies provide references for self-assessment index systems under the new public management philosophy for higher education in China.